2022
DOI: 10.1021/acsbiomaterials.2c01142
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Activated Thermosensitive Liposome–Gold Nanorod Hybrids for Enhanced Drug Delivery and Stimulus Sensitivity

Abstract: Combinatorial photothermal therapy and chemotherapy is an extremely promising tumor therapeutic modality. However, such systems still remain challenges in stimulus sensitivity, avoiding drug leakage, and therapeutic safety. To solve these problems, we engineered actively loaded doxorubicin (DOX) and gold nanorod (GNR) liposomes through embedding stiff hollow mesoporous silica nanoparticles (HMSNs) in the liposomal water cavity (HMLGDB) to resist the influence of shear force of GNRs to prevent drug leakage. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The fabrication process of GZABEF NPs is illustrated in Scheme a. First, GNRs absorbing in NIR-II were prepared by seed-mediated methods . The scanning electron microscopy (SEM) image revealed that the GNRs were 10 nm by 85 nm (aspect ratio = 8.5) (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication process of GZABEF NPs is illustrated in Scheme a. First, GNRs absorbing in NIR-II were prepared by seed-mediated methods . The scanning electron microscopy (SEM) image revealed that the GNRs were 10 nm by 85 nm (aspect ratio = 8.5) (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…First, GNRs absorbing in NIR-II were prepared by seedmediated methods. 18 The scanning electron microscopy (SEM) image revealed that the GNRs were 10 nm by 85 nm (aspect ratio = 8.5) (Figure 1a). According to the UV−vis spectra, the longitudinal surface plasmon band was located at 1060 nm (Figure S1).…”
Section: Synthesis and Characterization Of Gzabefmentioning
confidence: 99%
“…Nanoparticles need to overcome multiple barriers to accumulate in target tissues via blood circulation. The recognition and clearance mechanisms of the endothelial phagocytic system and the targeting ability of the nanoparticles are two of the most critical factors . Biomimetic modification of nanoparticles by using erythrocyte membranes where the CD47 membrane protein on the surface can establish self-recognition communication with the phagocytic system and evade recognition, phagocytosis, and clearance, thus enhancing the long cycling capacity of the nanoparticles .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the development of nanotechnology, nanoplatform provides a perfect loading and transport platform for targeted delivery and intelligent release of drugs such as small molecules, genes, peptides, inorganic materials, and therapeutic gases, which can effectively increase the targeted accumulation efficiency, improve pharmacokinetic properties, and reduce toxic effects of drugs. Gentle and noninvasive treatments have attracted a lot of attention due to their effective tumor-destroying ability and minimal harm to normal tissues . Photothermal therapy (PTT) has become an important research direction in anti-tumor research because of its safety, efficiency, and on-demand modifiability. …”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The development of photothermal therapy has been accelerated by significant research on NIR-sensitive photothermal agents, including organic small molecule dyes, conjugated polymers, and metallic plasmonic nanoparticles (e.g., gold nanorods and quantum dots). [6][7][8][9][10][11][12][13][14] These photosensitive materials are able to undergo photoexcitation, resulting in the production of thermal energy via the photothermal effect. [15,16] Among those NIR-sensitive reagents, small molecule organic dyes have attracted significant interest because of their low toxicity, excellent biocompatibility, and tunable spectral properties through structural modifications.…”
Section: Introductionmentioning
confidence: 99%